(untitled) (International Journal of Engineering and Computer Science, 2014)
This paper analyses the electric field effect on particle movement in three phase gas insulated busduct with different field calculation methods like analytical method(AM), charge simulation(CSM), and finite element methods(FEM). The presence of free metallic particles in GIB can result in loss of as much as 90% of the SF6 gas dielectric strength and can be a problem with Gas Insulated Substations (GIS) operating at high electric fields. The main objective of this paper is to derive techniques for formulating the basic equations that will govern the movement of metallic particles in GIB. The simulation has been carried out to obtain the particle trajectories at various voltages on Aluminium and Copper particles. From the simulation results it is observed that the Al and Cu particle movements are increasing with increase of applied voltage. From the results it can also be observed that the maximum radial movements of Al and Cu particles are relatively less when calculated using charge simulation method and relatively highest when calculated using finite element method. It is found that maximum radial movements computed using analytical method is slightly more than charge simulation method.